A Case of a Pathological Complete Response to Neoadjuvant Nivolumab plus Ipilimumab in Periampullary Adenocarcinoma. (26th May 2021) - Pothuri, Vikram; Herndon, John; Ballentine, Samuel J.; Lim, Kian‐Huat; Fields, Ryan C.
Abstract: Herein, we report on a patient with known Lynch syndrome and periampullary adenocarcinoma that exhibited a pathological complete response to neoadjuvant nivolumab plus ipilimumab. Two MSH2 mutations, high microsatellite instability, high tumor mutational burden, and elevated PD‐L1 expression were identified by next‐generation sequencing and immunohistochemistry. Following FOLFIRINOX (Fluorouracil/Leucovorin/Irinotecan/Oxaliplatin) administration and disease progression, nivolumab (1 mg/kg) and ipilimumab (3 mg/kg) were administered every 3 weeks for four total cycles. The patient responded well with minimal adverse effects and significant improvement in epigastric pain, appetite, and body weight. She then underwent resection consisting of pancreaticoduodenectomy, which demonstrated pathological complete response. Complete genomic profiling of periampullary carcinomas is crucial for optimal treatment selection as true ampullary masses and pancreatic ductal adenocarcinoma have different genetic profiles. This case provides an example of a patient who may have further benefited from first‐line nivolumab plus ipilimumab to avoid the reduced efficacy and significant side effects associated with chemotherapy. Key Points: A patient with known Lynch syndrome and ampullary adenocarcinoma harboring two MSH2 mutations, high microsatellite instability (MSI‐high), high tumor mutational burden (TMB), and elevated PD‐L1 expression achieved pathological complete response with neoadjuvant nivolumab plus ipilimumab. The combination of nivolumab plus ipilimumab may be a better first‐line option for patients with ampullary adenocarcinomas harboring deficient mismatch repair, MSI‐high, and high TMB. Complete genomic profiling of periampullary adenocarcinomas is crucial for optimal treatment selection as true ampullary masses and pancreatic ductal adenocarcinoma have different genetic profiles. The presence of either MSI‐high or high TMB could be an appropriate predictive biomarker for response to nivolumab plus ipilimumab in the context of Lynch syndrome. Abstract : This article reports the case of a patient with Lynch syndrome and periampullary adenocarcinoma, providing an example of a patient who may have benefited from first‐line nivolumab plus ipilimumab to avoid the reduced efficacy and significant side effects associated with chemotherapy.